Analysis of postoperative atrial fibrillation and its associated factors in Morrow procedures with cardiopulmonary bypass - Zhibin Hu; Wenshuai Mao; Lijun Guo; Zhiwei Liu; Xujie Hu; Yong Cui (BMC Cardiovascular Disorders)
Abstract Background The factors influencing the onset of new atrial fibrillation following the Morrow procedure due to cardiopulmonary bypass (CPB) are unclear. This study investigated the CPB-related factors associated with postoperative atrial fibrillation (POAF) in patients undergoing minimally invasive ventricular septal myectomy (Morrow procedure) to optimize CPB strategies, reduce the incidence of POAF, and enhance recovery. Methods A retrospective clinical data analysis was conducted on 139 patients who underwent minimally invasive Morrow procedures from January to December 2023. The patients were divided into two groups based on whether they developed new-onset atrial fibrillation after surgery, and a comparative study was performed. Multivariate regression analysis were used to assess factors potentially influencing POAF during CPB. Results Fifty (36%) patients developed POAF. Comparisons between the POAF group and the non-POAF group revealed significant differences in preoperative hypertension (38.0% vs. 14.6%, p = 0.002), ischaemic cardiomyopathy (40.0% vs. 20.2%, p = 0.012), history of heart failure (44.0% vs. 22.5%, p = 0.008), age (55.16 ± 14.11 vs. 46.28 ± 14.55, p = 0.001), the preoperative systemic immune-inflammation index (SII) (418.26 ± 243.97 vs. 330.24 ± 152.89, p = 0.019), the left atrial volume index (LAVI) (36.79 ± 12.08 vs. 32.24 ± 10.78, p = 0.024), CPB time (129.80 ± 39.58 vs. 116.96 ± 28.80, p = 0.027), CPB weaning time (25.68 ± 22.56 vs. 19.49 ± 6.78, p = 0.018), rate of re-CPB (14.0% vs. 3.4%, p = 0.020), rate of ultrafast-track cardiac anesthesia (UFTCA) (78.0% vs. 98.9%, p = 0.000), and ΔSII (2874.58 ± 2865.98 vs. 1981.85 ± 1519.89, p = 0.006) (P < 0.05). All patients were discharged, but the ICU (2.07 ± 2.91 vs. 1.38 ± 0.78, p = 0.046) and postoperative hospital stays (11.84 ± 7.50 vs. 9.13 ± 2.62, p = 0.002) were significantly prolonged. The results of the multivariate logistic regression analysis indicated that the occurrence of POAF was independently associated with age (OR = 1.047, 95% CI: 1.015–1.080), ΔSII(OR = 13.317, 95% CI: 3.103–57.154) and UFTCA(OR = 0.054, 95% CI: 0.006–0.493) (p < 0.05). Additionally, the increased value of SII was independently associated with CPB weaning time (t = 2.493, p = 0.014) and age(t=-2.270, p = 0.025). Conclusion UFTCA is a protective factor against POAF. Age and ΔSII are risk factors for the occurrence of POAF after the Morrow procedure. CPB weaning time and Age are significant influencing factors of ΔSII. Implementing UFTCA and shortening the CPB weaning time are expected to lower the risk of POAF, shorten ICU and hospital stays, and enhance recovery. Clinical trial number Not applicable.